2022
DOI: 10.1111/scs.13117
|View full text |Cite
|
Sign up to set email alerts
|

Parents' experiences with public health nursing during the postnatal period: A reflective lifeworld research study

Abstract: Aim To describe mothers' and fathers' experiences with public health nursing and child and family health centre services in the postnatal period, both as a couple and as individuals. Method A phenomenological reflective lifeworld research approach with a descriptive design was chosen. A purposive sample of 10 mothers and 10 fathers were interviewed twice, 1–2 and 6–8 weeks postpartum, using joint and individual interviews. By focusing on being open and flexible, the data were analyzed to elucidate a meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…Although it is the mothers who breastfeed, the midwives and PHNs highlighted the importance of understanding fathers' need for breastfeeding‐related counselling and care. This accords with Høgmo et al [49], who found that including the father in counselling gives families an increased feeling of mastering the breastfeeding situation.…”
Section: Discussionsupporting
confidence: 86%
“…Although it is the mothers who breastfeed, the midwives and PHNs highlighted the importance of understanding fathers' need for breastfeeding‐related counselling and care. This accords with Høgmo et al [49], who found that including the father in counselling gives families an increased feeling of mastering the breastfeeding situation.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research shows that there is a discrepancy between new mothers’ and fathers’ perceived need for care and support, and what they experience receiving ( Høgmo et al, 2021 ; Sacks et al, 2022 ). It has also been found that fathers’ need for follow-up is not recognized in the same way as the mothers ( Finlayson et al, 2023 ; Høgmo et al, 2023 ). This is reflected in the research, which largely focuses on mothers’ experiences with postnatal health care ( Finlayson et al, 2020 ; Slomian et al, 2017 ; Walker et al, 2019 ).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The postnatal period is often described as a stressful time in the life of parents, with an increased need for both information, clinical care and psychosocial- and emotional support in order to feel secure in the parenting role ( Høgmo et al, 2023 ; Wiklund et al, 2018 ). Achieving positive motherhood, fulfilling adaptation to changed intimate and family relationships, and regaining health and wellbeing after giving birth are important for new mothers ( Finlayson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that to help mothers become confident in their role and strengthen the family’s experience of handling the situation, healthcare professionals should include mothers’ partners in breastfeeding counselling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%